Orangtua Memilih Tidak Mendaftarkan Anak pada Lembaga PAUD. Apa Penyebabnya? - Kale, Sartika; Timo, Arwandi W. M; Mundiarti, Vanida; Oedjoe, Mintje Ratoe (Education For All, 2023)
PAUD (Early Childhood Education) institutions provide appropriate educational services for early childhood, as a form of preparation for children to enter the next level of education or elementary school level, but in society is that there are parents who do not register their children at PAUD institutions, so research this study aims to explore the factors that cause parents to choose to enroll their children in primary schools without going through guidance at PAUD institutions. This research is a qualitative research with a duration of six months. Data collection was carried out with four informants using data collection techniques through interviews and documentation studies. The results of the study showed that there were four factors that caused parents not to enroll their children in PAUD institutions, namely, the education factor, the job factor, the income factor, and the time factor. Parents should be able to register their children at early childhood education institutions, so that children are better prepared for higher education and as an effort to optimize children's growth and development through educational services that are appropriate to the child's age that can be obtained at early childhood education institutions.